VD_FINDINFO PPD 3/13 - 29/2013 vom 28. Oktober 2013 - VD Tribunal cantonal (2013)
DIVORCE, PARTAGESENS GÉNÉRAL, PRESTATION DE LIBRE PASSAGE, PRÉVOYANCE PROFESSIONNELLE, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 CC, 22 LFLP, 7 OLP, 12 OPP2